The Mediating Role of Consumer Trust in Influencing Student Orientation to Invest Using Ajaib App: A Framework Based on SEM-PLS - Ika Barokah Suryaningsih; Alis Puspita Dewi; Marmono Singgih; Sumani Sumani; Rizky Atika Salsabila Ivabianca Putri (University of Merdeka Malang, 2023)
This explanatory study aimed to examine the mediating role of consumer trust in influencing information quality and perceived security on intention to invest using the Ajaib Application. The data obtained by the distribution of online questionnaires. The sample used is 160 students in university. The data analysis conducted with SEM-PLS using SmartPLS 3. The results showed that both the information quality and perceived security, had a positive and significant effect on intention to invest. The results also indicate that consumer trust significantly mediates information quality and perceived security on intention to invest. It is recommended for companies to maintain the quality of existing information and improve application security in order to build the user trust so that they can encourage their intention to invest using the Ajaib application.